Development of Color-Based Object Follower Robot Using Pixy 2 Camera and Arduino to Support Robotics Practice Learning - Wahrini, Retyana (DPTE FT UNY, 2023)
The purpose of this study is to find out how robot vision works and the level of media feasibility in the robotic practice course and student responses in the Mechatronics Vocational Education study program. This research is a type of R&D research with a 4D development model (Define, Design, Development, and Desiminate). The result of how the vision robot works is where the robot follows objects based on color using the Pixy 2 camera that has been programmed in the PixyMoon application where the way this robot works is to follow the more dominant object. The results of the feasibility level of vision robots as learning media are determined by the results of the validation of media experts and material experts. Based on the results of the validation of media experts, the overall robot vision was declared very feasible with a percentage of 86.7%. Then from the results of material expert validation, it can be seen that overall, the robot vision companion guidebook is included in the very feasible category with a percentage of 87.5%. From the results of the assessment by students, it can be seen that from all aspects of the overall assessment it can be concluded that robot vision is in the very feasible category with a percentage of 90.8%.